From the Editor. - Philps, Alan (World Today)
An introduction is presented in which the editor discusses various reports within the issue including one by Gang Chen on ways to update the law of land tenure in China, another by Caroline Bay on hacking of Sony Pictures Entertainment Inc., and one on the disturbing aspect of the global city.